Expiration dates : a novel - Serle, Rebecca (Atria Books, 2024)
"Daphne Bell believes the universe has a plan in store for her. Ever since she was young, whenever she met a new guy, Daphne would find a slip of paper with exactly how long they'd spend together--4 months, two weeks, one night. That's how she met her ex-boyfriend and current best friend, Hugo, the only person in Daphne's life who knows of her secret. Followed by a string of men and countless dates, Daphne resigned herself to the fact that she was never meant to find the one, to be in love, until one night when she receives a paper on her way to a blind date, except this time, the paper is blank. Jake is everything you want in a guy--kind, hard-working, and perfectly handsome. But as they get to know each other and their relationship becomes increasingly more serious, Daphne wonders if this is the right path for her, and worries about the secrets she's hiding from Jake. When part of Daphne's past becomes a part of her present, she is forced to confront everything she's been hiding from the those she loves most and must make a pivotal decision to choose whether to live her life according to others, or herself. This story is about being single and searching for love, but it's also a story about destiny and what people mean to us."--